2012
DOI: 10.2116/analsci.28.887
|View full text |Cite
|
Sign up to set email alerts
|

Amino-functionalized Nano-size Composite Materials for Dispersive Solid-Phase Extraction of Phosphate in Water Samples

Abstract: An efficient analytical method for the preconcentration and determination of phosphate in water samples at trace levels was proposed. The method was based on sample enrichment using dispersive solid-phase extraction (dSPE) with tetraethylenepentamine (TEPA)-functionalized nano-size composite materials (TEPA-NCMs) as sorbents, which were fully characterized. Various parameters affecting the extraction efficiency were systematically investigated. After extraction, the post-adsorbed TEPA-NCMs were eluted by a NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Since the polymer shell was diamagnetism, it was reasonable that the ratio of paramagnetic composition reduced, which led to lower saturation moments than that of the bare Table 2. 16,19 With an increase of pH, the TEPA-Fe 3 O 4 -NMPs surface carried positive charge, and thus would more signicantly attract the negatively charged monovalent H 2 PO 4 À ions in solution, which indicated that the physicochemical adsorption due to electrostatic attraction was the predominant process of phosphate removal, as described by eqn (7). On the contrary, the concentration of the N element on their surfaces increased from 4.53% to 8.53%, with the usage amount of Fe 3 O 4 increasing from 0.5 g to 2 g, even though the total contents of the nitrogen decreased as founded in elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the polymer shell was diamagnetism, it was reasonable that the ratio of paramagnetic composition reduced, which led to lower saturation moments than that of the bare Table 2. 16,19 With an increase of pH, the TEPA-Fe 3 O 4 -NMPs surface carried positive charge, and thus would more signicantly attract the negatively charged monovalent H 2 PO 4 À ions in solution, which indicated that the physicochemical adsorption due to electrostatic attraction was the predominant process of phosphate removal, as described by eqn (7). On the contrary, the concentration of the N element on their surfaces increased from 4.53% to 8.53%, with the usage amount of Fe 3 O 4 increasing from 0.5 g to 2 g, even though the total contents of the nitrogen decreased as founded in elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been many signicant developments in the synthesis of magnetic nanoparticles, maintaining the stability of these particles for a long time without agglomeration or precipitation is an important issue. 16,17 With more and more strictly environmental regulations on the discharge of phosphorus and rising demands for clean water with extremely low levels of phosphorus, functionalized-magnetic nanoparticles, with enhanced adsorption rate, capacity, and selectivity, have gradually attracted researchers' great interest to be used as adsorbents for phosphorus removal. Functional polymers coating on the magnetic core enhanced the stability of nanodispersions by preventing their aggregation, moreover, the absorption properties can be tailored by suitable functional groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N1s high-resolution scan of nFe 3 O 4 @EDAMIP could be deconvoluted into two individual peaks at binding energies of 398.6 eV and 396.5 eV (Fig. 5b), which were assigned to the N atoms in C NH 2 and C NH C groups [26], respectively. A new peak at 399.8 eV was observed after 2,4,6-TCP adsorption, which could be attributed to the hydrogen bonding of ph O H· · ·NH 2 or N H· · ·O ph [27].…”
Section: Effect Of Ph and Adsorption Mechanismmentioning
confidence: 99%
“…The maximum percentage of extraction was achieved using bark ash of C. auriculata at a pH 10 in the presence of interfering cations (Mg 2+ , Cu 2+ , Zn 2+ , Fe 2+ and Ni 2+ ). Nano-size composite materials functionalized with amino groups were also used for phosphate extraction by Shen and co-workers [9]. The removal of arsenic species in water using the macrocycle known as calix [4] pyrrole has been discussed by Danil de Namor and co-workers [10].…”
Section: Introductionmentioning
confidence: 99%